Wind turbine installed in multifamily building: Profitable or not? Sustainable or not? (Scientia Agropecuaria, 2016)
The purpose of this study was to determine the economic and environmental sustainability of a horizontal wind turbine prototype installed in a multifamily building. Economic sustainability was determined by primary classic economic study and environmental sustainability using the emergy approach. The classic economic analysis indicates that the project is not profitable (NPV = -2971.05 US dollars), and the environmental analysis (percentage of renewability: 0.18, emergy yield rate: 1.23; environmental load rate: 4.48; energy sustainability index: 0.275; energy investment ratio: 4.35 and emergy exchange rate: 0.32) indicates a high dependence of the system regarding imported machineries, an average efficiency regarding the use of local resources for the benefit of society, low environmental impact and an average production cost over other electricity production processes.
Keywords: Economic analysis; emergy; wind turbine; wind power